SINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK KULIT BUAH NAGA SUPER MERAH (HYLOCEREUS COSTARICENSIS L.) SERTA KAJIAN PUSTAKA UNTUK KARAKTERISASI DAN UJI AKTIVITASNYA SEBAGAI ANTIMIKROBA - Fitria Wati, Afina
The widespread and inappropriate use of antibiotics has led to the emergence of antibiotic-resistant microbial phenotypes. Therefore, many attempts have been made to discover new classes of antimicrobial compounds. One of them is the development of nanoparticles. It is known that silver nanoparticles have good antimicrobial activity with a different mechanism from antibiotics. Therefore, silver nanoparticles were synthesized using a green synthesis approach because it has many advantages, namely simple, cost-effective, environmentally friendly, easy to scale up to mass production, and safe for therapeutic applications because it is biocompatible. Silver nanoparticles were synthesized using super red dragon fruit peel extract (Hylocereus costaricensis) as a reducing agent as well as a capping agent using the microwave irradiation method. Experiments and literature review were carried out to determine the optimum conditions for the synthesis of silver nanoparticles from dragon fruit peel extract, determine the characteristics (size and structure) of silver nanoparticles formed from biosynthesis using dragon fruit peel extract, and determine the antimicrobial and antifungal activity of silver nanoparticles formed from biosynthesis against bacteria Staphylococcus aureus, Escherichia coli, Mycobacterium smegmatis, and the fungus Candida albicans, Aspergillus niger. The synthesis was carried out using a concentration of 8 Mm AgNO3 solution with a ratio of the volume of AgNO3 solution: the volume of the extract solution was 3: 4 using a power of 50 P for 150 seconds at pH 8. The nanoparticles were then characterized using UV-Vis spectroscopy, Particle Size Analyzer (PSA), Fourier Transform Infrared Spectroscope (FTIR), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), and X-Ray Diffraction (XRD). UV-vis spectroscopic analysis showed SPR at 420 nm. PSA showed the diameter of the nanoparticles was 83.9 with a polydisspecificity index of 0.37. FTIR shows the functional groups involved in the synthesis of nanoparticles, including the functional groups of phenol, carboxylic acid, alkane, alkene, and carbonyl. SEM and TEM show spherical particles. XRD shows that the crystalline phase of the nanoparticles formed is face-centered cubic (FCC). The antimicrobial activity of silver nanoparticles was tested on the bacteria Staphylococcus aureus, Escherichia coli, Mycobacterium smegmatis, and the fungus Candida albicans, Aspergillus niger. The antimicrobial activity of silver nanoparticles is stronger in bacteria than fungi.